2018
DOI: 10.1186/s12889-018-5118-1
|View full text |Cite
|
Sign up to set email alerts
|

Spousal age difference and associated predictors of intimate partner violence in Nigeria

Abstract: BackgroundThe growth in Intimate Partner Violence (IPV) cases among couples in Nigeria has been significant in recent years. Victims, which are often females, face numerous health challenges, including early death. I examined the linkages between spousal age differences and IPV in Nigeria.MethodThe couples recode data section of the 2013 Nigeria Demographic Health and Survey was used (n = 6765). Intimate partner violence was measured using 13-item questions. Data were analyzed using the logistic regression mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
57
6
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(69 citation statements)
references
References 18 publications
(35 reference statements)
5
57
6
1
Order By: Relevance
“…A similar finding was reported by the study from Zambia indicating an increased risk of IPV as marriage duration increases [29]. The increased duration of marriage might lead to an increased risk of partner violence as factors such as having additional children and economic hardship put more demands and stress on the family [49].…”
Section: Plos Onesupporting
confidence: 85%
“…A similar finding was reported by the study from Zambia indicating an increased risk of IPV as marriage duration increases [29]. The increased duration of marriage might lead to an increased risk of partner violence as factors such as having additional children and economic hardship put more demands and stress on the family [49].…”
Section: Plos Onesupporting
confidence: 85%
“…People in close age groups most of the time compete in the same issues. This may lead them to physically express their feelings [39,40]. In support of this finding, a study carried out in Burkina Faso found the physical violence significantly decreases when the age difference is more than 15 years [41].…”
Section: Discussionmentioning
confidence: 92%
“…26 However, studies by Izmirli 2014 in Turkey and Adebowale 2018 in Nigeria showed that violence was higher among younger men. 27,28…”
Section: Discussionmentioning
confidence: 99%